2017
DOI: 10.1097/aap.0000000000000615
|View full text |Cite
|
Sign up to set email alerts
|

Preserved Analgesia With Reduction in Opioids Through the Use of an Acute Pain Protocol in Enhanced Recovery After Surgery for Open Hepatectomy

Abstract: A novel ERAS protocol for open hepatectomy successfully reduced reliance on perioperative opioids without expensing adequate analgesia compared with traditional care. Patients within ERAS benefitted from application of epidural, which further reduced opioid requirements and optimized pain control without increasing complication rates. Epidurals should remain an integral part of ERAS protocols for liver resection surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 22 publications
1
40
0
1
Order By: Relevance
“…5 The initial clinical findings suggested that ESPB injectant would spread to both the dorsal and ventral ramus of the spinal nerves, leading to blockage of both somatic and visceral pain, a effect similar to epidural analgesia. 6,7 Time is required to determine the exact features and effectiveness of this block, as well as its safety and feasibility in various surgical procedures and pain syndromes, using anatomic studies, case reports, and clinical studies of bilateral ESPB. The objective of this narrative review article is to review the relevant anatomy, describe the mechanism of spread of the injectant, demonstrate varying approaches to ESPB, and summarize case reports and clinical trials, as well as provide current insight on this emerging and popular block.…”
Section: Introductionmentioning
confidence: 99%
“…5 The initial clinical findings suggested that ESPB injectant would spread to both the dorsal and ventral ramus of the spinal nerves, leading to blockage of both somatic and visceral pain, a effect similar to epidural analgesia. 6,7 Time is required to determine the exact features and effectiveness of this block, as well as its safety and feasibility in various surgical procedures and pain syndromes, using anatomic studies, case reports, and clinical studies of bilateral ESPB. The objective of this narrative review article is to review the relevant anatomy, describe the mechanism of spread of the injectant, demonstrate varying approaches to ESPB, and summarize case reports and clinical trials, as well as provide current insight on this emerging and popular block.…”
Section: Introductionmentioning
confidence: 99%
“…The intrathecal injection of a small dose of morphine is an important part of the protocol and has significant benefits for pain control in the immediate postoperative period. Grant et al showed that the use of regional analgesia like epidural significantly decreased the amount of narcotics used on daily basis. But others have shown that the use of intrathecal injection of morphine is a safe procedure which is preferred over epidural to avoid the side effects of epidural anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…The economic costs of the opioid crisis in terms of increased healthcare and substance abuse treatment costs, lost productivity, and criminal justice costs is estimated at nearly US$80 billion 3. Since the perioperative period may be a vulnerable period for the development of long-term and persistent opioid use, the use of regional anesthesia as part of a multimodal analgesic regimen4 may decrease perioperative opioid consumption while providing at least equivalent postoperative analgesia compared with an opioid-based regimen5 and, as a result, may potentially contribute to a decrease in opioid use after surgery.…”
Section: Introductionmentioning
confidence: 99%